Analysis of Responsibility and Discipline Character Values in Students of the State Elementary School of 2 Hadipolo - Handayani, Nor; Riswari, Lovika Ardana; Santoso, Santoso (Universitas Pendidikan Indonesia Kampus Serang, 2023)
This study aims to elucidate elementary school students' responsibility and discipline characteristics. This research was carried out since problems existed regarding the lack of a sense of student responsibility and discipline, which included students not completing and submitting assignments promptly, students lacking in maintaining the cleanliness of the school environment, and a lack of students paying attention to the teacher during the learning process. This descriptive qualitative research used the case study method. Data collection methods employed in this research were observation, interviews, and documentation. Data analysis techniques encompassed data reduction, presentation, and conclusion drawing. Then, the subjects consisted of four students and one teacher in sixth grade. The results of this study highlighted that the roles of a sixth-grade teacher at the state elementary school of 2 Hadipolo in instilling the character of responsibility and discipline in sixth-grade elementary school students were by providing 1) routine activities at school to familiarize students, 2) exemplary and obedience to the regulation, which teachers could instill character by exemplifying good behavior based on regulation, and 3) for spontaneous reminding, teachers could instill character through spontaneous activities by reprimanding students violating the applicable rules at school. Further, school assignments and activities given to students could foster responsibility and discipline characters.